Interpersonal Markers of Taylor Swift and Armaya Doremi in Their Graduation Speech - Winalda, Gaizka Naufal; Indah, Rohmani Nur (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2023)
Public speaking, including presenting a graduation speech, becomes unintentionally complex because it has standardization. Presenting outstanding speeches becomes a challenge for English Foreign Language (EFL) learners, who delegate themselves as public speakers. This research compares graduation speeches by Taylor Swift, a native speaker, and Armaya Doremi, an EFL student. It is to identify the intricate skills that should be mastered in public speaking, namely using discourse markers. The descriptive qualitative method was used to find interpersonal markers used by Taylor Swift and Armaya Doremi. The theory used to analyze the data was the interpersonal marker theory by Ã„del (2010). The findings demonstrated that the interpersonal markers used in both graduation speeches were linguistic comments, discourse organization, speech act labels, and references to the audience. Taylor Swift, a native speaker, used all main categories of interpersonal markers and longer interpersonal markers than Armaya Doremi, as an EFL learner. Future researchers are suggested to dig deeper into the topic, particularly concerning interpersonal markers of spontaneous speech in various contexts.